Walkabout - Marshall, James Vance (Camberwell, Vic Puffin Books, 2009)
Mary and her brother Peter are the only survivors of an aircrash in the middle of the Australian outback. Facing death from exhaustion and starvation, they meet an aboriginal boy who helps them to survive, and guides them along their long journey. But a terrible misunderstanding results in a tragedy that neither Mary nor Peter will ever forget
1
Keywords: Arid regions -- Australia -- Fiction; Survival -- Fiction